CROWDSOURCING WEB MODEL OF PRODUCT REVIEW AND RATING BASED ON CONSUMER BEHAVIOUR MODEL USING MIXED SERVICE-ORIENTED SYSTEM DESIGN - Prastyo, Yuli Adam (PROCEEDING IC-ITECHS 2014, 2014)
AbstractThe existence ofinternetdrives many consumer behavior changes. Purchaseonline(e-commerce) isgrowing rapidlyled tothe assumption ofbehavioral changesprior tomaking a purchase. Consumerbehaviormodelsare5phasesfromneeds identification, information search, alternative evaluation, purchase decision, andpost-behavior. This model is phasesof before and after purchaseincludingonlinepurchasing behavior. Product informationhas spread on the internetin the form ofblogs, web commerce, orother. Buyer candidate needa lot of timetosearch product informationfrom previous users. Therefore, we need web as a bridge that canbring togetherthe information from experiencedusers and the need of product from buyer candidate.The concept ofcrowdsourcingis the right solutiontobethat bridge web.This studyaimedtofindthe crowdsourcingmodelof productreview andratingbasedon consumer behavior model. Research methodsinclude  surveys,  interviewsand  literature  studies.  Results  ofthe  research  is acrowdsourcingmodel ofwebof product reviewandrating using the concept ofa mixedservice- orientedsystem.This conceptis a blend ofSoftware-Based Services (SBS) and Human-Provided Services(HPS). The design ofthis model can be appliedin the developmentof web-based crowdsourcing.